2017
DOI: 10.1016/j.athoracsur.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Low Accuracy of Computed Tomography and Positron Emission Tomography to Detect Lung and Lymph Node Metastases of Colorectal Cancer

Abstract: Computed tomography and FDG-PET have limitations if the objective is to detect all malignant nodules and to discriminate the LNI in cases of pulmonary metastases of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…In our series and in accordance with what has been reported by the International Registry, only 6.9% of patients who underwent lymphadenectomy had histologically proven lymph nodal involvement although other authors have described this figure to range between 5% and 32% . We might hypothesize that the low prevalence of nodal metastases might be due to our close follow‐up protocol and the consequent early referral of patients and to the strict preoperative work‐up to select candidates for surgical treatment.…”
Section: Commentsupporting
confidence: 90%
See 2 more Smart Citations
“…In our series and in accordance with what has been reported by the International Registry, only 6.9% of patients who underwent lymphadenectomy had histologically proven lymph nodal involvement although other authors have described this figure to range between 5% and 32% . We might hypothesize that the low prevalence of nodal metastases might be due to our close follow‐up protocol and the consequent early referral of patients and to the strict preoperative work‐up to select candidates for surgical treatment.…”
Section: Commentsupporting
confidence: 90%
“…If the results will confirm a non‐inferiority of SBRT over surgery, the former might become an attractive option for this patients due to its lower invasiveness and reduced overall risks . However, it must be considered that, although the reported incidence of involved lymph nodes is not high, the CT scan has a high incidence of false‐negative and the positive predictive value of PET in detecting lymph node involvement is low, thus rendering histological confirmation necessary, even if the patient is offered a nonsurgical approach.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, new minimally invasive biopsy techniques (15,16) and high definition imaging rise doubts on unavoidability of such aggressive nodal assessment. Nevertheless, several studies reported an unexpected high occurrence of a node-positive occult disease in primary and secondary lung tumors (36)(37)(38)(39) probably due to microscopic lymph nodal involvement. Contrariwise, this happened in less than 4% of cases ACOSOG Z0030 trial (23); in this study, systematic nodal dissection showed no survival benefit of over nodal sampling (NS).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that the rate of unexpected lymph node metastases in renal cell cancer metastasectomy is high 23 and the accuracy to detect additional lung or lymph node metastases for chest computed tomography is low, 24 we did not perform a minimal invasive approach. By open approach we were able to palpate the lung, and the rate of detecting additional lung or lymph node metastases may be higher.…”
Section: Methodsmentioning
confidence: 99%